The Effects of Environmental Performance and Environmental Information Disclosure on Financial Performance in Companies Listed on the Indonesia Stock Exchange - Msy, Mikial (Archives of Business Research, 2019)
The objective of this study was to examine the effects of environmental performance and environmental information disclosure on financial performance in companies listed on the Indonesia Stock Exchange. The population in this study amounted to 20 companies listed on the Indonesia Stock Exchange, issued an Annual Report and Sustainability Report and included in the Sustainability Disclosure Database of the Global Reporting Initiative (GRI). The data used in the form of secondary data obtained from annual reports and sustainability reports of companies listed on the Indonesia Stock Exchange from 2013 to 2016. The numbers of observations in this study were 80. The analysis technique used was Partial Least Square (PLS). The novelty in this study is to measure environmental performance based on outcomes, namely environmental costs incurred by the company rather than compliance with regulations. The cost of a well-managed environment will improve environmental performance because there are efficient use of resources. The results of this study indicate that eenvironmental performance has no significant effect on financial performance, environmental information disclosure has a significant effect on financial performance. Disclosure of environmental information has a negative effect on financial performance, it shows that if the disclosure of environmental information is more equipped and in accordance with the disclosure guidelines, the cost is not small so that it will reduce financial performance. Research limitation that environmental costs is difficult to obtain so that the population is limited to companies listed on the IDX that have a Sustainability Report and are included in the Sustainability Disclosure Database of the Global Reporting Initiative. Disclosure of environmental information which is the result of the implementation environmental management accounting has not been done by all companies, because it is still voluntary is not mandatory. The suggestion of the research, the Indonesian Accountants Association is expected to form separate standards for measuring and reporting environmental cost information and standardized. For other researchers who are interested in researching environmental accounting can develop other variables for a longer time and the number of companies that publish more Sustainability Reporting.